THE MUSLIM WOMAN IN THE RUSSIAN EMPIRE IN CONTEMPORARY WESTERN SCHOLARSHIP (Journal of history, 2026)
The article is a historiographical analysis of modern foreign studies devoted to rethinking the role of Muslim women in the Russian Empire. The purpose of this article is a historiographical analysis of modern foreign studies devoted to rethinking the image and role of Muslim women in the Russian Empire. The methodological basis of the research is a critical analysis of foreign monographs and articles of the last thirty years, carried out within the framework of postcolonial theory, gender and intellectual history. The historiographical analysis focuses on the criticism of ideas about Muslim women as passive objects, on the study of their independence (agency) in the religious and legal spheres, as well as on the analysis of the interaction of imperial law with Sharia norms. The scientific novelty of the article lies in the fact that it not only provides a summary overview of these achievements, but also carries out their critical reflection through the prism of G. Spivak's methodology, revealing the regional and class limitations of the source base, as well as the risk of creating a new, academic representation. The result of the study is a comprehensive assessment of how modern Western historiography represents the Muslim woman as an active subject of history, as well as the identification of methodological challenges facing this field. This article contributes to the integration of new methodologies (postcolonial and gender-based) and the enrichment of the methodology framework within domestic historical science.
Keywords: Muslim women, Russian Empire, historiography, female agency, Jadidism, legal status, sharia, gender history.